Psychological well-being, basic psychological needs, and social support among Korean wheelchair curling players - Joung, H. J.; Lee, Y. (International Journal of Human Movement Science, 2018)
Drawing on basic need theory, we explored the relationships between psychological well-being (PWB), basic psychological needs (BPN), and social support (SS) among Korean wheelchair curling players. The purpose of this study is to examine the relationship between PWB, BPN satisfaction, and social support in Korean wheelchair curling players. Fifty-two elite wheelchair curling players registered at the Korea Wheelchair Curling Association (KWCA) were completed a survey. A questionnaire battery includes four categories: (a) a demographic characteristic questionnaire (8 items), (b) the Scales of Psychological Well-Being (SPWB; 16 items), (c) the Scales of Basic Psychological Needs (SBPN; 12 items), (d) Social Support Questionnaire (SSQ; 20 items). All data were collected using self-report questionnaires and analyzed using principle component analysis, Cronbach's a, descriptive statistics, correlation analyses, and robust multiple regression. The Cronbach`s alphas for PWB, BPN, and SS were 0.96, 0.85-0.95, and 0.74-0.90, respectively. Both BPN and SS were significantly correlated with PWB (p < .05). In the regression analysis, BPN and emotional support significantly predicted PWB, explaining 78.1% of the variance. From a theoretical perspective, these results support basic need theory; more practically, the results highlight the potential importance of strategies and environments that support basic need satisfaction and high-quality relationships.